The Peran Kepemimpinan Yayasan dalam Manajemen Sumber Daya Manusia Sekolah Swasta terhadap Kinerja Guru dan Kualitas Layanan Pendidikan - Az-Zahra, Fathimah; Ichsan Prastya Firmansyah; Aip Sarifudin; Mira Apriana Markus; Haniyyah; Winanti (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
Private schools managed by foundations often face challenges in human resource management, particularly when foundation leadership is less than optimal in providing organizational structures and work facilities for teachers. This study aims to analyse the influence of foundation leadership on school human resource management and its impact on teacher performance and the quality of educational services. Referring to the findings,(Hendra et al., nd)Emphasizing the importance of leadership and performance management in improving the quality of educational services, this study used a quantitative approach through a survey of teachers and education personnel. The results indicate that foundation leadership positively influences the effectiveness of human resource management, which in turn improves teacher performance and the quality of school services. These findings underscore the need for foundations to strengthen their support and human resource management systems to optimize the learning process.